USER EXPERIENCE ANSWER SYSTEM AUTOMATICALLY WITH USER CENTERED DESIGN AND USER EXPERIENCE QUESTIONNAIRE-SHORT - Sophia Nouriska; Meida Cahyo Untoro; Aidil Afriansyah; Mugi Praseptiawan; Winda Yulita; Ilham Firman Ashari (LPPM Nusa Mandiri, 2023)
The interface of the automatic answer assessment system is plagued by several issues, including an unfamiliar layout, unresponsive design, inconsistency in elements, and a lack of clarity in presenting information. These problems significantly hinder the overall user experience. As a result, this study aimed to address these challenges by designing a user-centered experience for the automatic answer assessment system, using a high-fidelity prototype tailored to meet user needs. The user-centered design method involved four crucial stages: Specify The Context Of Use, Specify Requirements, Create Designs, and Evaluate Designs. Through rigorous usability testing with teachers, the design achieved an impressive effectiveness rating of 90%, firmly establishing it as a